2018
DOI: 10.1159/000490858
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping in Sickle Cell Disease Patients: The French Strategy

Abstract: This review presents the French strategy for blood group genotyping in high-responder and newly diagnosed sickle cell disease (SCD) patients. In addition to FY, JK, and MNS genotyping, the RH blood group system is now explored in SCD patients in France. Molecular typing has been used for the deduction of partial RH2 (C) antigens since 2010, and the gradual implementation of systematic RHD and RHCE genotyping nationwide was initiated in late 2014. In our laboratory, 962 RH:2 (C-positive) SCD patients have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 45 publications
2
19
1
Order By: Relevance
“…Similar concepts for the extended matched blood supply are established in different countries worldwide [34,35,36,37]. …”
Section: Discussionmentioning
confidence: 99%
“…Similar concepts for the extended matched blood supply are established in different countries worldwide [34,35,36,37]. …”
Section: Discussionmentioning
confidence: 99%
“…No anti-D have ever been reported in carriers of RHD*DAU13 or RHD*DUC3, and the parallel c.48C>G substitution present in many African RHCE alleles is considered by some authors to be benign. 70,90 On the contrary, for the controversial RHD* weak partial D 4.0, 2, 43-45 many interactions differ from wild-type RhD (14 different interactions involving four residues and two protein domains), which would predict the risk of anti-D production. Compared to its high prevalence in individuals of North African descent, very few cases of anti-D production have been described for this variant, mostly not consistent with alloanti-D, 27,43,45 and autoadsorption studies are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…The association of c.48G>C and c.1136C>T (p.W16C and p.T379M) found in the RHD*DAU13 allele is probably not associated with the risk of anti‐D production either and does not warrant transfusion with D– RBC units. No anti‐D have ever been reported in carriers of RHD*DAU13 or RHD*DUC3 , and the parallel c.48C>G substitution present in many African RHCE alleles is considered by some authors to be benign 70, 90 …”
Section: Discussionmentioning
confidence: 99%
“…We have observed that when the molecular report does not provide an interpretation and recommendation, clinical practictioners not experienced in blood group genetics hesitate to interpret RHD genotyping results as D+ or D−. For the purposes of RhIG adminstration and transfusion, interpretation of an RHD genotype requires not only pertinent experience but also knowledge of the history 2,5 as well as the current evolving data [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] and literature reports 15,16,[23][24][25][26] of the risks for alloimmunization associated with specific RHD genotypes. 27 Hospital computer systems may require updating to accomodate new requirements, such as the ability to change a prior serologic D typing result, when it is overridden by a different D type based on RHD genotyping results.…”
mentioning
confidence: 99%